Relationship Between Soda-Free Diet and Nutritional Status in Teenagers: A Cross Sectional Study - Suharna, Anik; Setyawan, Yuswanto (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Excessive consumption of sugary beverages such as soda has become a significant public health concern worldwide, particularly due to its association with poor nutritional status and a heightened risk of overweight and obesity in adolescents. This study aimed to investigate the relationship between adherence to a soda-free diet and nutritional status among teenagers using Chi-square and Spearman correlation analyses. A cross-sectional design was employed involving 200 adolescents aged 15 to 18 years, who were categorized into two groups based on their soda consumption habits: soda consumers and those following a soda-free diet. Nutritional status was assessed by calculating Body Mass Index (BMI) and classifying participants into underweight, normal weight, and overweight/obese categories. The results indicated that teenagers who abstained from soda consumption had a significantly higher prevalence of normal weight (70.6%) compared to soda consumers (45.2%). Conversely, the rate of overweight and obesity was markedly higher among soda consumers (30.4%) than those on a soda-free diet (14.1%). Spearman’s correlation analysis revealed a strong positive relationship between the frequency of soda consumption and BMI (rho = 0.68, p < 0.001), suggesting that higher soda intake is closely associated with increased body weight. These findings emphasize the critical role that reducing soda consumption plays in improving nutritional health among adolescents. From a public health perspective, promoting soda-free diets and encouraging healthier beverage choices should be prioritized in nutrition education and obesity prevention programs targeting youth populations to reduce the risk of diet-related chronic diseases. Keywords: Soda-free diet, Nutritional status, Teenagers, BMI, Obesity prevention, Public health